Case Report: Advanced Skeletal Muscle Imaging in S-Adenosylhomocysteine Hydrolase Deficiency and Further Insight Into Muscle Pathology - Petković Ramadža, Danijela; Kuhtić, Ivana; Žarković, Kamelija; Lochmüller, Hanns; Čavka, Mislav; Kovač, Ida; Barić, Ivo; Prutki, Maja (Frontiers in Pediatrics, 2022)
Introduction: S-Adenosylhomocysteine hydrolase deficiency (SAHHD) is a rare inherited multisystemic disease with muscle involvement as one of the most prominent and poorly understood features. To get better insight into muscle involvement, skeletal muscles were analyzed by magnetic resonance imaging (MRI) and MR spectroscopy (MRS) in three brothers with SAHHD in the different age group. Method: The study was based on analysis of MRI and MRS of skeletal muscles of the lower and the proximal muscle groups of the upper extremities in three SAHHD patients. Results: Three siblings presented in early infancy with similar signs and symptoms, including motor developmental delay. All manifested myopathy, more pronounced in the lower extremities and the proximal skeletal muscle groups, and permanently elevated creatine kinase. At the time of MRI and MRS study, the brothers were at age of 13, 11, and 8 years, respectively. MRI revealed lipid infiltration and MRS curve showed an elevated muscle lipid fraction (higher peak of lipid) which increased with age, and was more prominent in the proximal skeletal muscles of the lower extremities. These results were consistent with muscle biopsy findings in two of them, while the third patient had no specific pathological changes in examined muscle tissue. Conclusions: These findings demonstrate that an accessible and non-invasive method of MRI and MRS is useful for an insight into the extent of muscle involvement, monitoring disease progression, and response to treatment in SAHHD.